Tetrandrine, an immunosuppressive alkaloid isolated from Steohania tetrandra S. Moore, induces the generation of Treg cells through enhancing fatty acid oxidation. Issue 4 (2nd June 2022) - Fang, Yulai; Zhang, Qin; Yuan, Xusheng; Lv, Changjun; Zhang, Jing; Zhu, Yanrong; Wei, Zhifeng; Xia, Yufeng; Dai, Yue
Abstract: Our previous studies have demonstrated that tetrandrine can induce the generation of regulatory T (Treg) cells in vitro and in vivo. But, the underlying mechanism of tetrandrine remains obscure. Naïve CD4 + T cells are isolated from the mesenteric lymph nodes of mice for the differentiation of Treg cells. Flow cytometry is used to detect the frequencies of Treg cells. Non‐targeted metabolomics analysis based on UHPLC‐QTOF/MS is performed to assess the intracellular metabolic profiles. ChIP‐PCR analysis is conducted to detect the level of H3K27ac at Foxp3 promoter and CNS regions. Tetrandrine treatment alters the metabolic profile of Treg cells, and pathway enrichment of differential metabolites mainly involves fatty acid oxidation (FAO). Tetrandrine promotes the mRNA expression of carnitine palmitoyl transferase‐1, and increases the level of acetyl coenzyme A (acetyl‐CoA) and the intracellular oxygen consumption rate. Either CPT1 inhibitor (etomoxir) or siRNA markedly diminishes the promotion of tetrandrine on Treg cell differentiation. Furthermore, tetrandrine enhances the acetylation of H3K27 in the promoter and CNS1 regions of Foxp3 through the acetyl‐CoA derived from FAO. In the mice with collagen‐induced arthritis, tetrandrine also induces Treg cell generation through FAO pathway. In addition, tetrandrine enhances the immunosuppressive function of Treg cells both in vitro and in vivo. The findings indicate that tetrandrine promotes Treg cell differentiation by enhancing FAO‐mediated Foxp3 acetylation, and the CPT1‐mediated FAO can serve as the target for the discovery of novel inducers of Treg cell generation. Abstract : Tetrandrine promotes Treg cell differentiation by enhancing CPT1‐mediated fatty acid oxidation. Mechanistically, tetrandrine treatment accumulates fatty acid oxidation product acetyl‐CoA, leading to an increase in H3K27 acetylation of Foxp3.